Book Review: J. Ikerd, A Revolution of the Middle… and The Pursuit of Happiness, on-line audiobook - Pawłowski, Lucjan (Problemy Ekorozwoju, 2011)
The wisdom in this book is drawn from forty-years of study, experiences, and observations as an economist at four major state universities and in communities all across North America and around the world. Professor J. Ikerd spent the first half of his career as an advocate of conservative, free-market economic thinking before concluding that the neoclassical concept of capitalism is simply not sustainable.